2023
DOI: 10.3390/nu15204432
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acid Levels in Maternal and Cord Plasma Are Associated with Maternal Socioeconomic Status

Alexandra Hergenrader,
Matthew VanOrmer,
Rebecca Slotkowski
et al.

Abstract: Omega-3 (n-3) polyunsaturated fatty acids (PUFAs) play a crucial role in fetal growth and neurodevelopment, while omega-6 (n-6) PUFAs have been associated with adverse pregnancy outcomes. Previous studies have demonstrated that socioeconomic status (SES) influences dietary intake of n-3 and n-6 PUFAs, but few studies have evaluated the association between maternal and cord plasma biomarkers of PUFAs and socioeconomic markers. An IRB-approved study enrolled mother–infant pairs (n = 55) at the time of delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Overall dietary quality improved with higher levels of education, with a greater effect in non-Hispanic White and Hispanic individuals compared to non-Hispanic Black individuals, demonstrating the intersectional socioeconomic factors that affect diet adequacy. A study in a different cohort demonstrated higher -3 FA concentrations in serum of college-educated ꞷ pregnant individuals compared those who had not completed a college education 48 . These studies emphasize the importance of identifying barriers to accessing recommended foods, including cost and/or knowledge of dietary recommendations, and suggest that there may be opportunities for targeted interventions in socially disenfranchised subpopulations.…”
mentioning
confidence: 97%
“…Overall dietary quality improved with higher levels of education, with a greater effect in non-Hispanic White and Hispanic individuals compared to non-Hispanic Black individuals, demonstrating the intersectional socioeconomic factors that affect diet adequacy. A study in a different cohort demonstrated higher -3 FA concentrations in serum of college-educated ꞷ pregnant individuals compared those who had not completed a college education 48 . These studies emphasize the importance of identifying barriers to accessing recommended foods, including cost and/or knowledge of dietary recommendations, and suggest that there may be opportunities for targeted interventions in socially disenfranchised subpopulations.…”
mentioning
confidence: 97%